2005
DOI: 10.1017/s1014233900001942
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral community selection and the genetic structure of a local goat breed in Patagonia

Abstract: SummaryThe effect of human intervention on the structure of locally adapted breeds in America is analyzed using the case of a rural community in Patagonia (Argentina) and its goats. The Neuquen Criollo Goat is analyzed focusing on the artificial selection practiced by the local rural community and its effects on the current type's distribution. Goatherd preferences in the selection of replacements were studied by means of a survey (n= 242). The distribution of 634 females of various types was recorded and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Whether permanent or transhumant, after five centuries of coevolution, one can expect that indigenous societies that fully embraced livestock raising have co-constructed particular niches with them. While some research exists regarding the different roles that livestock have had in the Americas’ post-conquest development (e.g., Melville, 1994 ; Camou-Healy, 1998 ; Narchi et al, 2015 ), few have approached them as protagonists of biocultural diversity persistence and evolution, as well as biodiversity promotion (e.g., Perezgrovas, 2004 ; Lanari et al, 2005 ).…”
Section: Old World Livestock Species In the Americasmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether permanent or transhumant, after five centuries of coevolution, one can expect that indigenous societies that fully embraced livestock raising have co-constructed particular niches with them. While some research exists regarding the different roles that livestock have had in the Americas’ post-conquest development (e.g., Melville, 1994 ; Camou-Healy, 1998 ; Narchi et al, 2015 ), few have approached them as protagonists of biocultural diversity persistence and evolution, as well as biodiversity promotion (e.g., Perezgrovas, 2004 ; Lanari et al, 2005 ).…”
Section: Old World Livestock Species In the Americasmentioning
confidence: 99%
“…On separate investigations, Lanari et al (2005) have been studying related and overlapping Argentinian socioecological systems in the northern province of Neuquén ( Table 2 ). Their focus, however, is on ethnozoology instead of ethnobotany.…”
Section: Old World Livestock Species In the Americasmentioning
confidence: 99%
“…Another group of authors looked at the function of livestock in the production system and at its relevance and importance for the livelihood of farmers (Markemann et al 2009;Gebre et al 2012). Other authors investigated local or indigenous selection criteria and breeding objectives practised in various production systems (Adams et al 2002;Jaitner et al 2003;Lanari et al 2005;Wurzinger et al 2006;Ndumu et al 2008;Kassie et al 2009;Duguma et al 2011). Gizaw et al (2010) show that adaptive traits, such as resistance to a disease, can be equally or even more important than production traits.…”
Section: Understanding Production Systems and Defining Breeding Objecmentioning
confidence: 99%
“…In north and central Neuquén, small holders breed local Criollo goat mainly for meat production. Lanari et al (2005) reported that directional selection practices by herdsmen were the main factors in adaptation and micro-evolution of Criollo goat populations in their native environments.…”
Section: Selection Of Heat Tolerant/genetic Traits For Adaptationmentioning
confidence: 99%